Assessing the Effects of Anthropogenic Land Use on Soil Infiltration Rate in a Tropical West African Watershed (Ouriyori, Benin) - Quentin Fiacre Togbévi; Martine van der Ploeg; Kéhounbiova Audrey Tohoun; Sampson K. Agodzo; Kwasi Preko (Applied and Environmental Soil Science)
Soil infiltration at a watershed scale is important for understanding and predicting the hydrological process in soil-water-plant systems. This study investigated the effects of land use (LU) conversion on the infiltration rate in the Ouriyori watershed. To that end, in situ infiltration was carried out over the watershed under thirty-six pairs of adjacent cropland-fallow plots using the hood infiltrometer. Saturated hydraulic conductivity (Ks), soil properties, and soil classes were further compared. Results showed a high variability of Ks following the LU classes with a coefficient of variation greater than 60%. After data log transformation, the mean values of Ks showed high infiltration and ranged between 2.59 and 2.42 cm d−1, respectively, for fallow land and cropland. Thus, Ks was relatively lower in cropland compared to fallow land. Hence, the low infiltration recorded in croplands indicated the degradative impacts of unceasing tillage operations for crop production without crop residue incorporation into the soil during tillage. There was no significant difference in bulk density and soil texture in both types of land use. Considering soil classes, the highest infiltration rate was found in Ferric Luvisol and the lowest rate in Dystric Gleysol, meaning that the high infiltration observed in Ferric Luvisol was due to the abundance of soil macropores. Change in natural vegetation to croplands induced a low infiltration rate and macropore connectivity. Moreover, fallow lands tend to provide water storage capacity through the improvement of mesopores, while soil compaction through agricultural activities reduces soil porosity and therefore soil infiltration. In addition, the paired Student’s t-test performed on the transformed data was statistically significant, indicating a difference between Ks under cropland and Ks under fallow land. To improve soil and water conservation for crop production as well as for sustainable rural populations’ livelihoods in the watershed, occasional fallowing may be observed to dampen infiltration hindering soil surface conditions.